Protease Nexin 1 Is Expressed in the Human Placenta - White, Elizabeth A; Baker, Joffre B; McGrogan, Michael; Kitos, Paul A (Thrombosis and Haemostasis, 1993)
Protease nexin 1 (PN1), a serine protease inhibitor that inactivates thrombin, urokinase, and plasmin, is produced abundantly in cultures of human fibroblasts and rat and human glioma cells. The major sites of PN1 synthesis in vivo and the specific physiological function(s) of this serpin are unknown. Using Northern blot analysis and a full-length PN1 cDNA probe we demonstrated the presence of PN1 mRNA in human term placentas. In situ hybridization of placental tissue with a PN1 riboprobe showed that PN1 mRNA is present throughout the placenta and is also abundant in the placental membranes. Immunohistochemical analysis with an anti-PN1 antibody showed co-localization of PN1 and its mRNA within the placenta.